Alien fraction of Chernihiv urban flora: analysis and checklist - Zavyalova, Liudmyla V. (Biodiversity: Research and Conservation, 2008)
The results of complex analysis of alien species of the urban flora of Chernihiv (Forest zone of Ukraine) are presented. The total nonnative flora of Chernihiv includes 263 species. It comprises 25% of the total number of the urban flora species. Following groups prevail in ecological, geographical, life forms and coenotic spectra of the alien fraction of the urban flora: submesophytes, those of Mediterranean origin, annual, ruderal plants. After its taxonomic structure the studied urban flora is similar to the zonal flora of Polissya, but has closer relations to the flora of the ancient Mediterranean area due to its synanthropization.